Is Nutrient Quality of the Locally-Existing, EAT-Lancet-like Plant-Based Diet Better or Worse than the Average Diet in Taiwan? An Example of Local Translation - Pan, Wen-Harn; Wu, Szu-Yun; Chang, Po-Chen (Nutrients, 2024)
The EAT-Lancet commission advocated a planetary health diet in 2019. Some have raised concerns about its nutrient adequacy. This study used data from recent Nutrition and Health Surveys in Taiwan—from 2017 to 2020 (n = 6538)—to assess food intake and nutrient adequacy among three red meat consumption levels (low/medium/high). The low red meat group, whose diet was similar to the EAT-Lancet reference, showed significantly higher/better levels of vitamins C and E, calcium, magnesium, sodium, dietary fiber, and the polyunsaturated to saturated fatty acids ratio. However, protein, B vitamins, phosphorus for females, and zinc were slightly compromised, but they were still near or above 100% of the Daily Reference Intakes (DRIs), except for zinc (74~75%). The intake levels of vitamin D, calcium, and dietary fiber in all three groups at times did not reach 70% of the DRIs, but this was more pronounced in the high red meat group compared to the low red meat group. Replacing ultra-processed foods (UPFs) with whole/healthy foods improved levels of zinc, calcium, and dietary fiber, but not vitamin D. Finally, a proposed local planetary health dietary construct was provided, suggesting maintaining the original distribution of the food groups recommended by the Taiwan Food Guide while specifying amounts of protein sources in line with the EAT-Lancet principles. The proposed diet, according to our estimation and comparison with Taiwanese DRIs, was nearly perfect in its nutrient composition.